Características determinantes del acceso a un empleo formal para las mujeres en Colombia (2017)
In Colombia, there has been research on inequality between men and women, as well as female labor participation, but one can still go deeper into the last one. This work consists of a study of various variables or characteristics of women in Colombia, and their influence in whether they access a formal job or not. It has been observed that women have an excessive burden of housework, which can hinder their participation in the formal labor market due to requiring greater flexibility of time in their work. Thus, the document presents a general framework on what has been studied regarding this problem and proposes a methodology that aims to approach the problematic in a more precise way through various control variables. This paper uses the round of 2013 of the Colombian Longitudinal Survey (ELCA) for the construction of a model through which an econometric estimate is obtained for the probability that women have to participate in a formal labor market. However, the results are not supposed to be interpreted generalizing for the Colombian case, because the base used is limited to households and individuals surveyed from 1 to 4 socioeconomic levels in urban areas.--Tomado del Formato de Documento de Grado.